Kesiapan Siswa yang Ditinggalkan Orangtua dalam Menghadapi Ujian - Mandar, Siltia; Syahniar, Syahniar; Syukur, Yarmis (Universitas Negeri Padang, 2017)
Readiness is the overall condition of a person who makes ready to respond/ answer in a certain way to a situation. Readiness is defined in this study is in the examination readiness. Examination is a way how to know the understanding of lesson level has been studied by student. The fact at the school, a lot of students have bad prepare to take examination. This research is descriptive and aimed to description about the prepare of students whose are left by their parents to take examination. This research can be conclude that the prepare of students whose are abandoned from their parents to take examination is good category. Implications of guidance and counseling services of the students whose are left by from their parents to take examination through of content services, placement and distribution services, group counseling and individual counseling